Experimental measurement and numerical validation of sloshing effects on resistance increase in head waves. (15th August 2021) - Zhu, Zhang; Lee, Jaehak; Kim, Yonghwan; Lee, Jae-Hoon; Park, Tae-Hyun
Abstract: Most sea trials of large merchant ships are carried out with the filling ballast water in cargo, and the trial environment may involve mild waves as well. It causes the ship to undergo a coupling effect between external wave excitation and internal sloshing motion, and an understanding of such coupling is important to analyze the components of the total resistance measured in sea trials. In this study, a blunt modified Wigley equipped with two inner tanks is selected to observe its hydrodynamic responses under head waves, using both experimental measurement and numerical computations. Ship is considered to have a forward motion at the Froude number of 0.2, and three filling conditions varying from low filling to high filling have been arranged for two inner tanks. For validation, numerical computation is performed based on the three-dimensional Rankine panel method with the linearized boundary value problems. Both seakeeping and internal sloshing flow are analyzed using the linear potential theory. The validation presents a sufficient agreement between experimental measurement and numerical results with or without the sloshing effect, and both two methods have shown that the sloshing coupling effect is generally insignificant for present ship model. However, when the wave encounter frequency becomes very close to the tank natural frequency, the medium filling tanks generate a strong coupling effect which can restrain ship motion responses as well as added resistance. Highlights: Sloshing effect on added resistance is considered in the viewpoint of sea trial. Towing tank test and linear potential-based method are carried out for the blunt modified Wigley hull. Ship mean trim is found to be restrained by the inertia effect of inner sloshing tank. Strong sloshing coupling effect is only observed at the resonant condition of medium filling tank. The strong coupling effect is found to reduce the added resistance in regular and irregular waves.